Budaya Salam Sapa Sebagai Manifestasi Sila Ketiga Pancasila : (Studi Pada Interaksi Sosial Di Fakultas Ilmu Sosial Unimed) - Griyani Elisabeth Purba; Nike Margaretha Br Sembiring; Rani Oktavia Purba; Tessa Lonika Simanullang (Universitas Palan, 2024)
In research conducted at the Unimed Faculty of Social Sciences, the culture of greetings as a manifestation of the Third Principle of Pancasila was investigated. The culture of greetings is a form of social interaction that involves the use of greetings or greetings when communicating with other people. This research aims to understand how the greeting culture is implemented in social interactions at the Unimed Faculty of Social Sciences. In the context of Pancasila, the Third Principle